Exploring Students’ Preferences in Using Platform for English Learning: LMS Or WhatsApp Group - Burhanuddin, Ahmad; Sofa, Eros Meilina (Lingual Journal of Language and Culture, 2024)
This qualitative study investigates two questions: (1) factors that lead to the tendency of students to use WhatsApp Groups compared to LMS E-Learning at UIN K.H Abdurrahman Wahid Pekalongan? (2) What features do students like on WhatsApp Groups in online learning. This research involved 100 students of the English Department UIN K.H Abdurrahman Wahid Pekalongan? The research findings reveal that (1) Students choose to use WhatsApp (WA) over the Learning Management System (LMS), because WA provides more convenience in terms of ease of access, interaction and communication, ease of navigation, learning experience and motivation, and better understanding of the material. (2) The features in WA that are liked by students are the auto-login feature, text and audio messages that facilitate interaction with friends or lecturers, where this feature cannot be found in the LMS and that WA is easier to use. In the eyes of students, the data security factor is still of less concern than the convenience and speed, which indicating the lack of awareness towards digital security.